Low-dose naltrexone for treatment of pain in patients with fibromyalgia: a randomized, double-blind, placebo-controlled, crossover study - Kirsten Bested; Lotte M. Jensen; Trine Andresen; Grete Tarp; Louise Skovbjerg; Torben S.D. Johansen; Anne V. Schmedes; Ida K. Storgaard; Jonna S. Madsen; Mads U. Werner; Anette Bendiksen (PAIN Reports, 2023)
Abstract. Introduction:. Fibromyalgia (FM) is a chronic fluctuating, nociplastic pain condition. Naltrexone is a µ-opioid-receptor antagonist; preliminary studies have indicated a pain-relieving effect of low-dose naltrexone (LDN) in patients with FM. The impetus for studying LDN is the assumption of analgesic efficacy and thus reduction of adverse effects seen from conventional pharmacotherapy. Objectives:. First, to examine if LDN is associated with analgesic efficacy compared with control in the treatment of patients with FM. Second, to ascertain the analgesic efficacy of LDN in an experimental pain model in patients with FM evaluating the competence of the descending inhibitory pathways compared with controls. Third, to examine the pharmacokinetics of LDN. Methods:. The study used a randomized, double-blind, placebo-controlled, crossover design and had a 3-phase setup. The first phase included baseline assessment and a treatment period (days −3 to 21), the second phase a washout period (days 22–32), and the third phase a baseline assessment followed by a treatment period (days 33–56). Treatment was with either LDN 4.5 mg or an inactive placebo given orally once daily. The primary outcomes were Fibromyalgia Impact Questionnaire revised (FIQR) scores and summed pain intensity ratings (SPIR). Results:. Fifty-eight patients with FM were randomized. The median difference (IQR) for FIQR scores between LDN and placebo treatment was −1.65 (18.55; effect size = 0.15; P = 0.3). The median difference for SPIR scores was −0.33 (6.33; effect size = 0.13; P = 0.4). Conclusion:. Outcome data did not indicate any clinically relevant analgesic efficacy of the LDN treatment in patients with FM.